The Effectiveness of Slow Stroke Back Massage, Counterpressure Massage, Cinnamon Aromatherapy on Dysmenorrhea in Adolescents - Gita Ayu Indria; Uti Lestari; Elita Sekar Wulandari; Ajeng Sekar Hanafi (Indonesian Journal of Global Health Research, 2026)
Menstrual disorders are commonly experienced by adolescent girls and may occur due to various factors, including hormonal production, stress levels, nutritional status, daily activities, and early age at menarche. Dysmenorrhea, or menstrual pain, is classified as a type of menstrual disorder. Non-pharmacological or complementary therapies can be provided to help reduce dysmenorrhea.  This research aims to determine the impact of providing interventions in the form of slow stroke back massage, counterpressure massage, and cinnamon aromatherapy for adolescent girls experiencing menstrual pain. The researcher employed a quasi-experimental method with a non-equivalent control group design, involving adolescent females divided into two groups. The researcher employed a quasi-experimental design with a non-equivalent control group, involving female adolescents as the study population and those experiencing dysmenorrhea as the sample. The participants were divided into two groups: an intervention group (n = 10), which received the treatment, and a control group (n = 10), which did not receive any intervention. A non-random sampling technique was used to recruit the participants. To measure pain intensity scores, a Numeric Rating Scale (NRS) was used. The collected data were analyzed using the Mann–Whitney test. The findings indicate that the intervention administered to the experimental group was effective in reducing pain, as demonstrated by the Mann–Whitney test comparing post-test pain scores between the experimental and control groups (U = 7.0, Z = −3.539, p < 0.001). The median pain score was lower in the experimental group (3; IQR 2–4) than in the control group (4; IQR 3–5). Interventions in the form of slow stroke back massage, counterpressure massage, and cinnamon aromatherapy were proven to be effective in reducing menstrual pain among adolescent girls.